GOVERNMENT ACTION IN THE PREVENTION OF SUSPECTED FRAUD (FRAUD) TRANSFER OF DATA MEMBERSHIP GUARANTEE PROGRAM HEALTH IN LEBAK REGENCY - Rachmatullah, Firman; Fasyehhudin, Mohamad Fasyehhudin; Ikomatussuniah, Ikomatussuniah (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Health Insurance is a guarantee that participants obtain health care benefits and protection in meeting basic health needs provided to every person who has paid contributions or whose contributions are paid by the government. The existence of fraud (Fraud) in the implementation of Public Health Insurance can be interpreted as an unlawful act committed by people from within and/or outside the organization, with the intention of obtaining personal or group benefits which directly harm other parties, One form of fraud that is detrimental to the community is the transfer of membership data without the knowledge or wishes of the community as participants in the National Health Insurance program. This research aims to analyze government actions in preventing fraudulent transfer of participant data as well as the effectiveness and efficiency of procedural data transfer for National Health Insurance program participants in the Lebak Regency area. The research method used is empirical juridical carried out to obtain clarity and understanding of research problems based on existing reality. The data collection technique involves collecting and reviewing existing regulations, followed by conducting in-depth interviews with office holders who are directly related to the data protection policy for National Health Insurance Program participants. The results of this research show that fraud prevention measures have been taken, but the weak implementation of sanctions according to existing regulations has not had a deterrent effect on the perpetrators. To be more effective and efficient in protecting participation data, support from all elements of society and the injured party is needed to report it so that individuals who commit fraud can immediately be given warnings and sanctions and preventive measures can be taken to prevent repeat cases. The results of this research show that fraud prevention measures have been taken, but the weak implementation of sanctions according to existing regulations has not had a deterrent effect on the perpetrators. To be more effective and efficient in protecting participation data, support from all elements of society and the injured party is needed to report so that individuals who commit fraud can immediately be given warnings and sanctions and preventive measures can be taken to prevent repeat cases It is hoped that this research can evaluate and determine risk mitigation efforts for factors that can influence the occurrence of fraud and as additional literature that can be used by Regional Governments to prevent fraud.